Diversity of vespid wasps (Vespidae: Hymenoptera) in Lang Son province - Phuong Lien, Nguyen Thi (Academia Journal of Biology, 2017)
Species diversity and abundance of vespid wasps (Vespidae: Hymenoptera) in Cai Kinh, Lang Son is examined. A total of 42 species in 20 genera of vespid wasps are recognized in Cai Kinh. They are 12 social wasp species belonging to 2 subfamilies, Polistinae (12 species) and Vespinae (3 species), and 27 solitary wasps belonging to the subfamily Eumeninae. The nest of Polistes strigosus is described for the first time. The genus Oreumenes of the subfamily Eumeninae is newly recorded for the Vietnamese fauna, represented by Oreumenes decoratus (Smith). The diversity of vespid wasps in the study area during three years (2014, 2015 and 2016) is compared showing that the diversity and evenness index are highest in 2016 (summer), meaning that many vespid species are active in summer. Eumenes quadratus and Delta ensuriens are most abundant in number of specimens. Received 02 December 2016, accepted 20 December 2016